Historical Kyoto : - Plutschow, Herbert E. (Japan Times, 1983)
Historical Kyoto presents a new and unique approach to the history of Kyoto, the former capital of Japan, in which specific sites in and around the city are identified with historical events. yet, because of Kyoto's signifficance in Japan's history, this books can also be read as a cultural history. Through this combination of history anf geography, the more than 1000 years of Kyoto's history come alive.